2022
DOI: 10.46303/repam.2022.7
|View full text |Cite
|
Sign up to set email alerts
|

Through the Eyes of Novice Teachers: Experiences with Professional Cultures Within and Outside of Neoliberal “No-Excuses” Charter Schools

Abstract: As neoliberal education reforms spread globally, including the development of school choice pathways that create different types of schools, a reexamination of teacher professionalism may be in order. Current literature about teacher experiences with neoliberal reforms often focuses on negative aspects of organizational professionalism and managerialism, describing shifts in professionalism as stifling teacher autonomy and diminishing satisfaction through increased accountability, standardization, and supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Torres (2014) has described teacher autonomy as "a cornerstone of the charter school movement" (p. 3). The literature on teacher autonomy in charter schools is mixed with some studies suggesting that charter school teachers experience greater autonomy than TPS teachers, but others suggest that there may be limits to this within larger CMOs (e.g., Waychunas, 2022). Conversely, Oberfield (2017) found some evidence that charter school teachers had more autonomy than teachers who work in TPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Torres (2014) has described teacher autonomy as "a cornerstone of the charter school movement" (p. 3). The literature on teacher autonomy in charter schools is mixed with some studies suggesting that charter school teachers experience greater autonomy than TPS teachers, but others suggest that there may be limits to this within larger CMOs (e.g., Waychunas, 2022). Conversely, Oberfield (2017) found some evidence that charter school teachers had more autonomy than teachers who work in TPS.…”
Section: Discussionmentioning
confidence: 99%
“…Fusco (2017) has termed large CMOs like KIPP, Uncommon Schools, Achievement First, and Success Academies as "burnout factories" -a nod to their long hours and high attrition rates. By contrast, Waychunas (2022) found that teachers in "no excuses" charter schools "created professional subcultures where novice teachers feel simultaneously challenged and supported" (p. 56).…”
Section: Teacher Burnoutmentioning
confidence: 99%
“…Fusco (2017) has termed large CMOs like KIPP, Uncommon Schools, Achievement First, and Success Academies as "burnout factories" -a nod to their long hours and high attrition rates. By contrast, Waychunas (2022) found that teachers in "no excuses" charter schools "created professional subcultures where novice teachers feel simultaneously challenged and supported" (p. 56).…”
Section: Teacher Burnoutmentioning
confidence: 99%